FinTech regulation and the development of the FinTech sector in the European Union - Radosław Ciukaj; Mateusz Folwarski (Journal of Banking and Financial Economics (JBFE), 2023)
The aim of the article is to identify the relationship between the level of regulation of various segments of the FinTech industry and the level of development of this sector. To address this research problem, the paper analyses the scope of regulation in 14 segments of the FinTech sector, and based on that, develops the FinTech Regulation Index for the individual European Union countries. Then, the paper uses this index to examine if there is a relationship between the level of regulation and the level of FinTech development in the various European Union countries. The econometric analysis confirmed the initial hypothesis that there is a significant relationship between the level of FinTech sector regulation and the level of its development.
Keywords: G2; G23; 330; FinTech; FinTech Regulation Index; digital innovations